A cross-sectional survey of medical and other groups' awareness, perceptions, and willingness to use e-cigarettes during the COVID-19 pandemic - Ruihang Deng; Chuang Yang; Yifang Yuan; Lifang Liang; Xin Yang; Xinyu Wang; Jiao Tian; Yuxin Zhang; Xuekai Wu; Haiyun Dai (Frontiers Media S.A., 2024)
BackgroundIn China, people's perceptions towards electronic cigarettes during Corona Virus Disease 2019 (COVID-19) pandemic compared with pre-pandemic conditions have not been explored. Exploring the perceptions of medical workers regarding e-cigarettes is crucial, as they serve as a trusted source of information and providers of smoking cessation counselling for smokers. This cross-sectional study was designed to explore the awareness and perceptions of e-cigarettes among Chinese medical and other groups in the context of the COVID-19 pandemic.MethodsA cross-sectional survey was performed using an online, anonymous, and self-administered questionnaire. The questionnaire contained sections for collecting participants' general information and Likert scale questions regarding smoking status, perceptions of e-smoking, attitude, and willingness to use e-cigarettes. The respondents included medical students, clinical doctors, and other occupations. Data analysis was performed using tools such as descriptive analysis, binary logistic regression, and multivariate regression.ResultsA total of 952 people completed the questionnaire, and 96.54% of them reported to have heard about e-cigarettes. The most common source of information about e-cigarettes was advertising. Notably, 28 of the 116 smokers reported that they had used e-cigarettes. Independent-samples T-tests results showed that medical groups believed e-cigarettes contained tar (p = 0.03). Most of the medical and non-medical participants maintained neutral attitudes towards e-cigarette policies (38.3%) and prices (49.2%) but their views were significantly different (p < 0.001). Multivariate logistic regression indicated that highly educated people had higher knowledge about e-cigarettes relative to those with lower education (undergraduate, OR = 1.848, 95CI% = 1.305-2.616, p = 0.001; master's degree or doctoral degree, OR = 1.920, 95CI% = 1.230-2.997, p = 0.004). The medical group used fewer e-cigarettes compared to non-medical group (OR = 1.866, 95CI% = 1.185-2.938, p = 0.007), the non-traditional cigarette users showed lower utilization compared to traditional cigarette users (18-40, OR = 4.797, 95CI% = 0.930-24.744, p = 0.061; > 40, OR = 9.794, 95CI% = 1.683-56.989, p = 0.011) and the older adult used fewer than the young (18-40, OR = 4.797, 95CI% = 0.930-24.744, p = 0.061; > 40, OR = 9.794, 95CI% = 1.683-56.989, p = 0.011).ConclusionThis study found that individuals tend to hold negative attitudes towards the awareness, perceptions, and willingness to use e-cigarettes. Medical groups are less likely to use e-cigarettes, but misperceptions are still prevalent among them. This calls for additional training for such medical personnel to improve their capacity to provide necessary counselling to smokers. E-cigarettes advertisements were the main source of information for young individuals to learn about e-cigarettes, and hence measures should be taken to restrict exposure of young individuals to e-cigarettes.